School textbooks of Soviet Kazakhstan: visual content and their role in ideological education - Bekmagambetov, Ruslan K.; Bekmagambetova, Maisara J.; Bimoldanova, Aigul A. (The New Research of Tuva, 2025)
The article analyzes the visual content of school textbooks published in the Kazakh SSR during 1955–1986. In Soviet Kazakhstan, students were educated using both USSR textbooks and those published within the republic. The source base consisted of the textbooks themselves, including “Bukvar” (Alphabet), “History of the USSR”, and “History of the Kazakh SSR”.The study is grounded in the peculiarities of the Soviet education system, of which the Kazakh system was a part, characterized by a close connection between knowledge and upbringing. Every element of the educational process, including the content and structure of textbooks, was required to conform to the ideological principles of the socialist state. School textbooks became an effective mechanism for indoctrinating Soviet ideals. Visual elements in the textbooks played a significant role in transmitting these principles.The article presents the regulatory framework governing textbook publications, illustrating the fully state-controlled process.Analysis revealed that visual images conveyed the ideological values of the specified era: educating students in the spirit of Soviet patriotism, loyalty to the Soviet people, the Communist Party, and the Soviet government; nurturing the spirit of friendship among peoples and proletarian internationalism. The visual information was aimed at shaping the Soviet person with corresponding values.In Kazakh textbooks, following the pattern of union-wide ones, the oppressive pre-revolutionary period contrasted with the prosperous Soviet era. These textbooks also contained local specifics: depiction of traditional life, symbols, images, and portraits of Kazakh figures.
Keywords: school textbook; illustration; Soviet ideology; visual content; Kazakhstan